2018
DOI: 10.1111/bcp.13732
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors for prescription of psychotropics and mood‐stabilizing antiepileptics during pregnancy in Denmark 2000–2016

Abstract: The use of APs, ADs and mood-stabilizing AEDs during pregnancy has increased substantially in Denmark from 2000-2016. The use of ADs appears to be slightly in decline since 2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
(57 reference statements)
3
10
0
Order By: Relevance
“…1 Flowchart over the study design. 1 Women with pre-pregnancy diabetes mellitus (type 1 or 2). 2 Use of valproate during pregnancy.…”
Section: Drug Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…1 Flowchart over the study design. 1 Women with pre-pregnancy diabetes mellitus (type 1 or 2). 2 Use of valproate during pregnancy.…”
Section: Drug Exposurementioning
confidence: 99%
“…The use of second-generation antipsychotic drugs (S-GAs) has more than doubled in the last decade, mainly explained by a wider spectrum of indications than for the first-generation antipsychotics (F-GAs), for example bipolar disorder [1][2][3][4][5][6][7]. The S-GAs have less extrapyramidal and prolactin-related side effects than F-GAs, but there are concerns regarding their metabolic side effects [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In such a context, the relationship between changes in antiepileptic drug prescribing during pregnancy and risk of malformation has become a public health interest in a few countries. [16][17][18][19][20][21][22] We performed a descriptive, population-based pharmacoepidemiological study using data from administrative healthcare databases aimed to evaluate prescription profiles of AEDs in an Italian population of women in childbearing age and pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Antidepressants are frequently used in the treatment of depression and anxiety disorders. Epidemiological studies suggested that antidepressant usage among pregnant women increased by 3‐ to 7‐fold in the past 2 decades and that up to 13% of fetuses are exposed to antidepressants 9‐11 . Although there are controversial results and low absolute risks reported in the literature, concerns still continue about the use of antidepressants during pregnancy.…”
mentioning
confidence: 99%
“…Epidemiological studies suggested that antidepressant usage among pregnant women increased by 3-to 7-fold in the past 2 decades and that up to 13% of fetuses are exposed to antidepressants. [9][10][11] Although there are controversial results and low absolute risks reported in the literature, concerns still continue about the use of antidepressants during pregnancy. In the past 2 decades, the body of published data on the use of antidepressants during pregnancy from epidemiological and clinical investigations has dramatically increased.…”
mentioning
confidence: 99%